Jom-lah fikir: a guide on transforming thoughts for your well-being - Phang, Cheng Kar (Department of Psychiatry & Mental Health, Faculty of Medicine & Health Sciences, Universiti Putra Malaysia, 2014)
Jomlah fikir is a book on managing our thoughts so that they're positive and helpful. this is important as it helps us to overcome excessive stress, prevent depression and generate happiness. Though it appears simple, this is based on scientific research and practice of cognitive behavior therapy, and the emerging field of positive psychology.